IMPLEMENTATION OF CASE METHOD IN CALCULUS COURSE - Kurniawan, Indra; Rahadyan, Andri (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2024)
This study aims to examine the application of the Case Method in teaching Calculus courses, focusing on enhancing student participation, learning motivation, and multi-directional communication in the context of both online and offline learning, thereby creating a dynamic and lively classroom. The research method used is descriptive with a qualitative approach, where descriptive analysis and literature review are used as the main techniques for data analysis. The subjects of this study are students who participate in learning using the Case Method. The instrument used for data collection is task-based interviews, which allow for the collection of qualitative data regarding students' experiences and perspectives related to this method. The results of the study show that students with high abilities can follow the learning process with the Case Method very well, students with moderate abilities can follow it well, and students with low abilities can follow it fairly well. The discussion of these results highlights how the Case Method can enhance student engagement and learning motivation across different ability levels and create effective communication in learning. The implementation of this research emphasizes the importance of adapting the Case Method in teaching to create an interactive learning environment that supports the development of communication skills and active student participation, both in online and offline learning